PENGARUH CASH TURNOVER DAN WORKING CAPITAL TURNOVER TERHADAP KINERJA KEUANGAN DIMEDIASI PROFITABILITAS PADA “PT .MEKAR KINANTI DAN LINTANG KEJORA” SEMARANG PERIODE TAHUN 2013 – 2017 - Patricia Dhiana Paramita (Universitas Pandanaran, 2019)
Financial performance is very important for a company. To see the company's financial performance can be seen from the level of profitability achieved for thecompany in a certain period of time. The profit of a company can be seen from the cashturnover and the company's working capital turnover, as well as